2017
DOI: 10.1002/glia.23188
|View full text |Cite
|
Sign up to set email alerts
|

KIAA1199: A novel regulator of MEK/ERK‐induced Schwann cell dedifferentiation

Abstract: The molecular mechanisms that regulate Schwann cell (SC) plasticity and the role of the Nrg1/ ErbB-induced MEK1/ERK1/2 signalling pathway in SC dedifferentiation or in myelination remain unclear. It is currently believed that different levels of MEK1/ERK1/2 activation define the state of SC differentiation. Thus, the identification of new regulators of MEK1/ERK1/2 signalling could help to decipher the context-specific aspects driving the effects of this pathway on SC plasticity.In this perspective, we have inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…KIAA1199, also defined as cell migration inducing protein (CEMIP), has been reported to be overexpressed in many cancers and promoted cancer metastasis through different signaling pathways, such as Wnt signaling and MEK1/ERK1/2 signalling [ 26 , 27 ]. Evensen et al found KIAA1199 was upregulated in breast cancer metastatic tissues, and resulted in EMT in breast cancer cells, inhibited cell migration in vitro and decreased metastasis in vivo [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…KIAA1199, also defined as cell migration inducing protein (CEMIP), has been reported to be overexpressed in many cancers and promoted cancer metastasis through different signaling pathways, such as Wnt signaling and MEK1/ERK1/2 signalling [ 26 , 27 ]. Evensen et al found KIAA1199 was upregulated in breast cancer metastatic tissues, and resulted in EMT in breast cancer cells, inhibited cell migration in vitro and decreased metastasis in vivo [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for investigating PKA and PKC is further supported by the evidence that the modulatory effects of PKA and PKC are involved in the activation of ERK pathway and transcription factors that regulate receptors (Cornelison et al, ; Liu, Chen, Liedtke, & Simon, ; Seybold, ; Wang, Cao, Liu, & Liu, ). Our findings were in agreement with other studies showing that elevated levels of ERK, PKA and PKC in TGs contribute to peripheral sensitivity (Boerboom, Reusch, Pieltain, Chariot, & Franzen, ; Cornelison et al, ; Wang et al, ; Yuan et al, ). We also confirmed that SP upregulated p‐ERK1/2, RAS, B‐Raf, PKA and PKC pathways under inflammatory conditions.…”
Section: Discussionsupporting
confidence: 93%
“…IL27RA might participate in immune regulation in CNS (Iwasaki et al, 2015;Yoshida and Hunter, 2015). CEMIP may be related to brain function and development (Yoshino et al, 2017(Yoshino et al, , 2018, MEK/ERK-induced Schwann-cell dedifferentiation (Boerboom et al, 2017), immune response in glioblastoma (Motaln et al, 2012), and WNT signaling (Li et al, 2017;Duong et al, 2018;Liang et al, 2018). It was frequently reported in colorectal cancers as well (Fink et al, 2015;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%